PTU-311 Endoscopy in variceal bleeding: optimal time to rescoping. (22nd June 2015) - Nunn, L; Shekhar, C; Mohammad, R; Fisher, N; Ishaq, S
Abstract : Introduction: Variceal haemorrhage is a common and potentially lethal complication of cirrhosis. 1 Variceal rebleeding can occur in 20% of cases in the first week following the acute episode. 2 BSG guidelines published in 2000 suggested endoscopy at weekly interval, whereas the AASLD guideline from 2007 suggest at 1–2 week interval and most recent ASGE guideline suggests optimal rescoping intervals of 1–8 weeks, a wide-ranging time scale recommendation classified as low-grade evidence. 3–5 There is also primary literature that indicates that rescoping in less than 3 weeks might increase risk of harm. 6 We have reviewed our practice to assess compliance with guidelines. Method: We carried out a retrospective review of endoscopic procedures and follow up after oesophageal variceal bleeds at a DGH in the West Midlands over a 12-month period from August 2012 onwards. We recorded the date of their first variceal bleed (index bleed) and the scheduled follow up endoscopy procedure. We also recorded any adverse events such as rebleeds (bleeds in <7 days since the index bleed) or interval bleeds (bleeds that occurred >7 days post index bleed). Results: 31 patients identified during 12 month period had total 45 acute variceal bleeds, requiring urgent endoscopy. Haemostasis was achieved in all but one occasion 97.8% (44/45), with the majority (32) receiving band ligation and remaining receiving sclerotherapy or combination of therapies. 20% of total bleeds had rebleeds or died within 7 days. Of the remaining 36 bleeds, 14% had scheduled repeat endoscopy in <7 days as per last BSG guidelines, 29% had scheduled endoscopy between 1–8 weeks, which conforms to the standards suggested in new ASGE guideline, 20% had follow up endoscopy after 8 weeks, and 37% had no follow up endoscopy. The mortality rates of the people rescoped within 0–2 weeks and 2–8 weeks were 78% and 23% respectively with multiple reasons contributing. Conclusion: There is inconsistency in the duration to follow up endoscopy practice perhaps due to wide discrepancy in available guidance and patient compliance. It is likely that in real life practice in UK, rescoping interval is variable and inconsistent. It would be helpful to reassess current BSG guidelines and consider follow up endoscopy within 3–8 weeks after an index variceal bleed, with ongoing prospective review and audit to inform future adjustment. Disclosure of interest: None Declared. References: Fortune and Garcia-Tasao, 2014 Bosch and Berzigotti, 2008 Gastroenterol Endosc. 2014;80(2) Gut, 2000;46(S3) Hepatology 2007;6(3) Harewood, Baron and Song, 2006 Ishaq S. Gastrointest Endosc. 2015, in press